Clinical significance of total nucleated cell count in bone marrow of patients with acute lymphoblastic leukemia who underwent allogeneic hematopoietic stem cell transplantation - Nukui, Jun; Tachibana, Takayoshi; Miyazaki, Takuya; Tanaka, Masatsugu; Matsumoto, Kenji; Ishii, Yoshimi; Numata, Ayumi; Nakajima, Yuki; Matsumura, Ayako; Suzuki, Taisei; Izumi, Akihiko; Hirose, Natsuki; et al. (International journal of hematology, 2024)
The clinical implications of recipient bone marrow nucleated cell count (NCC) prior to allogeneic hematopoietic stem cell transplantation (allo-HSCT) remain unknown. We conducted a multicenter retrospective study to evaluate the clinical significance of bone marrow NCC prior to allo-HSCT in patients with acute lymphoblastic leukemia. Patients who were in remission and underwent the initial allo-HSCT were included and stratified into high- and low-NCC groups using an NCC of 10 × 10 4 /µL as the cut-off. The 3-year overall survival (OS), non-relapse mortality (NRM), and relapse rates for the high- and low-NCC groups were 51.2 vs. 84.5% ( p < 0.001), 27.5 vs. 6.5% ( p < 0.001), and 31.1 vs. 24.4% ( p = 0.322), respectively. The high-NCC group had significantly poorer OS and higher NRM when compared with the low-NCC group. In summary, high recipient bone marrow NCC is associated with higher NRM and lower OS following allo-HSCT.